2007
DOI: 10.1002/mar.20158
|View full text |Cite
|
Sign up to set email alerts
|

Workplace isolation: Exploring the construct and its measurement

Abstract: Virtual offices are a growing trend in today's work environment and are expected to influence marketing roles dramatically, especially selling. These conditions may lead to perceptions of isolation, both socially and organizationally. Workplace isolation is a two-dimensional construct that represents individuals' perceptions of isolation from others at work and includes perceived isolation from both colleagues and from the company's support network. This article reports the results of a four-sample study to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
177
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(202 citation statements)
references
References 63 publications
4
177
0
9
Order By: Relevance
“…According to Marshall et al (2007), researchers have identified isolation perceptions as one of the major issues that people working in virtual office would experience. An employee's workplace isolation usually results from the perceptions that they are lacking the chance to interact with co-coworkers, and they are not part of the group, and they can't get the support or recognition from the co-workers and supervisors when they are in need (Marshall et al, 2007). This kind of isolation perception would be stronger for the employees who are working in the remote offices because the opportunities for networking and interactions are less compared to the ones who working in traditional office.…”
Section: Social Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Marshall et al (2007), researchers have identified isolation perceptions as one of the major issues that people working in virtual office would experience. An employee's workplace isolation usually results from the perceptions that they are lacking the chance to interact with co-coworkers, and they are not part of the group, and they can't get the support or recognition from the co-workers and supervisors when they are in need (Marshall et al, 2007). This kind of isolation perception would be stronger for the employees who are working in the remote offices because the opportunities for networking and interactions are less compared to the ones who working in traditional office.…”
Section: Social Relationsmentioning
confidence: 99%
“…Virtual employees believe that they are recognized as less committed to their tasks by their supervisors, and assigned less visible projects, and provided less feedback and mentoring or even less career support (Marshall et al, 2007). All these lead to the perceptions of inappropriate achievement recognition, which further related to employees' job satisfaction.…”
Section: Achievement Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited opportunities for personal interaction appear to be detrimental to morale, which leads to poor performance and a lower quality of service delivered to customers. Research has demonstrated a correlation between frequency of communication and interpersonal trust, organizational commitment, and a sense of affiliation with the organization (Marshall, Michaels, & Mulki, 2007). In order for individuals to see the value of organizational membership, a high level of contact is required between management and employees, as well as between employees and their peers.…”
mentioning
confidence: 99%
“…Brignall III and Van Valey (2005) stress that computer-mediated communication (CMC) is not the problem per se; the key lies in determining how to make use of this tool in order to bond socially with telecommuters. The importance of creating situations that facilitate casual interactions, friendship, and camaraderie must not be underestimated (Marshall et al, 2007). …”
mentioning
confidence: 99%